The ECJ’s Apple Judgement: A Game-Changer in the Architecture of EU Taxation or Just a Story of Procedural Defeat? - Allevato, Giulio (Rivista di Diritto Tributario, 2024)
Through its judgement of 10 September 2024, the European Court of Justice closed the Apple State aid case, that is the largest tax case in history, as it is worth € 13 billion. Contrary to most experts’ expectations, the Court of Justice overturned the General Court’s judgement and ruled in favor of the Commission, thereby upholding the qualification of two advance tax rulings granted by the Irish tax authorities to the Apple group as illegal State aid and condemning Ireland to recover an unprecedented amount of money. At first glance, such outcome seems to be in apparent contrast with the Court of Justice’s own recent case law (in particular, the Fiat and Amazon judgements), which had established that a correct interpretation of Art. 107 TFEU prohibits the use of external standards not incorporated into national law – such as the OECD guidelines on transfer pricing in the case of Luxembourg and Ireland – to determine the reference system for State aid purposes. However, some elements and recent developments may induce to minimize the effects of the Apple judgement on the architecture of EU taxation.
Keywords: State aid; Tax ruling; APA; Apple; Arm’s Length Principle; ALP; 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas